18F-FDG Brain PET/MRI in Amyotrophic Lateral Sclerosis– Frontotemporal Spectrum Disorder (ALS-FTSD) - Mashriqi, Faizullah; Mishra, Bibhuti B.; Giliberto, Luca; Franceschi, Ana M. (World Journal of Nuclear Medicine, 2023)
Amyotrophic lateral sclerosis (ALS) is a fatal and progressive neurodegenerative disorder involving both upper and lower motor neurons. Interestingly, 15 to 41% of patients with ALS have concomitant frontotemporal dementia (FTD). Approximately, 50% of patients with ALS can copresent with a broader set of neuropsychological pathologies that do not meet FTD diagnostic criteria. This association resulted in revised and expanded criteria establishing the ALS-frontotemporal spectrum disorder (FTSD). In this case report, we review background information, epidemiology, pathophysiology, and structural and molecular imaging features of ALS-FTSD.
Keywords: amyotrophic lateral sclerosis; amyotrophic lateral sclerosis-frontotemporal spectrum disorder; 18F-FDG; PET/MRI; brain PET